Association between incidental dose outside the prostate and tumor control after modern image-guided radiotherapy. (January 2021) - Witte, Marnix; Pos, Floris; Incrocci, Luca; Heemsbergen, Wilma
Abstract: Background and purpose: External beam radiotherapy for prostate cancer deposits incidental dose to a region surrounding the target volume. Previously, an association was identified between tumor control and incidental dose for patients treated with conventional radiotherapy. We investigated whether such an association exists for patients treated using intensity modulated radiotherapy (IMRT) and tighter margins. Materials and methods: Computed tomography scans and three-dimensional treatment planning dose distributions were available from the Dutch randomized HYPRO trial for 397 patients in the standard fractionation arm (39 × 2 Gy) and 407 patients in the hypofractionation arm (19 × 3.4 Gy), mainly delivered using online image-guided IMRT. Endpoint was any treatment failure within 5 years. A mapping of 3D dose distributions between anatomies was performed based on distance to the surface of the prostate delineation. Mean mapped dose distributions were computed for patient groups with and without failure, obtaining dose difference distributions. Random patient permutations were performed to derive p values and to identify relevant regions. Results: For high-risk patients treated in the conventional arm, higher incidental dose was significantly associated with a higher probability of tumor control in both univariate and multivariate analysis. The locations of the excess dose mainly overlapped with the position of obturator internus muscles at about 2.5 cm from the prostate surface. No such relationship could be established for intermediate-risk patients. Conclusions: An association was established between reduced treatment failure and the delivery of incidental dose outside the prostate for high-risk patients treated using conventionally fractionated IMRT.